Mentzer Index as a Screening Tool for Detecting Iron Deficiency Anemia Keeping Serum Ferritin as Gold Standard - Bibi, Jaweria; Bibi, Saima; Swati, Bibi Tayyaba; Anees, Aleena; Butt, Alvina (Indus Journal of Bioscience Research, 2025)
Background: Iron-deficiency anemia remains a prevalent condition in children, with considerable effect on their development and growth. Early and accurate diagnosis is essential to effective management, particularly in a setting of low resources. The Mentzer index has been proposed to be a good screening tool for IDA based on its low cost and simplicity of performance, although its diagnostic accuracy regarding serum ferritin levels must be established. Objective: To determine the diagnostic accuracy of Mentzer index in detecting iron deficiency anemia taking serum ferritin as gold standard in children. Study Design: Cross-sectional validation study. Duration and Place of Study: The study was conducted from April 2024 to October 2024 at the Department of Pediatrics Medicine, ATH Abbottabad. Methodology: A total of 162 children aged 1 to 5 years, presenting with symptoms suggestive of IDA, were enrolled through convenient sampling. The Mentzer index was calculated for each participant, and serum ferritin levels were measured. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy were calculated for the Mentzer index using a 2x2 contingency table to compare with the serum ferritin test. Results: The study found that the Mentzer index demonstrated high sensitivity of 91.6% and specificity 87%)for diagnosing IDA in children. The diagnostic accuracy was 90%, with a PPV of 91% and an NPV of 88%. Stratified analysis indicated better performance in rural populations (sensitivity 93%, specificity 88%) compared to urban areas (sensitivity 67%, specificity 87%). Gender-based differences were observed, with males showing a higher PPV (97%) compared to females (77%). Conclusion: The Mentzer index is a reliable, cost-effective screening tool for iron deficiency anemia in children, particularly in resource-constrained settings.